Расширение функциональных свойств экспертной системы определения неисправностей электрических машин - Дурницкая, Ольга Анатольевна; Карпенко, Евгений Александрович; Огарь, Вита Александровна (НТУ "ХПИ", 2010)
Principles of construction of consulting model of determination of disrepairs of electric machines on the basis of external signs are considered. A mathematical description of architecture of consulting model is given and user facilities which broaden functional possibilities of consulting model are grounded.
Expansion of functional properties of consulting model of determination of disrepairs of electric machines
Keywords: система электромеханическая; диагностика; система информационная; динамический обмен данными; база данных